The development of MHE brand equity from international students’ perspective - Maulan, Suharni; Muhammadun Mohamed, Zakiah; Mohd Yasin, Norjaya (2010)
This study aims to examine factors that contribute to the development of Malaysia Higher Education (MHE) brand equity from the international student’s perspective. As the higher education becomes more internationally oriented, the competition in the industry globally also becoming more intense. This forces the education service providers to differentiate their offerings from those of their competitors and one of the ways is through branding. As a business firm with high brand equity can differentiate itself from competitors, so too a nation in terms of their higher education services offerings. A strong brand equity of higher education service will give signal to customers during their pre-purchase evaluation thus facilitates them to make choice decision. Three focus group discussions with international students currently studying in a Malaysian public university had been conducted. The findings supported that MHE brand awareness and MHE brand image combined, affect MHE brand equity. MHE brand awareness is influenced by personal and commercial sources while MHE brand image is further influenced by country and institution image. The positive country image performs halo effects on institution image in which it affects prospects belief on product attributes and eventually choice decision. However, for consumers, their actual experiences will directly affect MHE brand equity.